Social inequalities in COVID-19-related years of life lost in metropolitan France, 2020 - Romana Haneef; Nour Mahrouseh; Pascal Bessonneau; Stephanie Vandentorren; Nicolas Minier; Francis Chin; Olivier Bruyère; Brecht Devleesschauwer; Grant M. A. Wyper (Archives of Public Health)
Abstract Background The COVID-19 pandemic has directly, and indirectly, exacerbated existing social health inequalities. People living in socially deprived areas are at greater risk of most adverse outcomes from COVID-19. The aim of this study was to quantify the extent of social inequalities in COVID-19 related YLL (Years of Life Lost) in metropolitan France during 2020. Methods The French national mortality database was used to identify COVID-19 related deaths. The French deprivation (FDep) index was used to assign deaths to a municipality-based social deprivation quintile of the French metropolitan population. Residual life expectancy at age of death was defined using the Global Burden of Disease (GBD) 2019 reference aspirational life table, and YLL was estimated for each registered death. Health inequalities were measured using gap measures between least and most deprived areas (absolute and relative), distributional measures (slope index of inequality (SII), relative index of inequality (RII)) and measure of potential impact (population attributable fraction (PAF)). The PAF was estimated using the least socially deprived quintile (Q1) as the reference level. Results In 2020, the overall age standardized YLL rate related to COVID-19 per 100 000 population was 836, ranging from 831 in the least deprived quintile (Q1) to 1058 in the most deprived quintile (Q5), reflecting the non-linear distribution between deprivation quintiles and COVID-19 YLL. The absolute gap was 227 and relative range was 1.27. The SII was 234.3 [95% confidence interval (CI): 226.6–241.9] COVID-19 YLL age standardized per 100 000 population. The rate in the most deprived areas (Q5) was around 67% higher than the mean population rate (RII = 1.33). The PAF estimate was not consistent (PAF = 0.36%) with gap and distributional measures of inequality. Conclusions COVID-19 cause-specific mortality was unequally socially distributed across areas. Our analysis highlighted marked inequalities in YLL estimates across urban and rural municipalities of France, the more disadvantaged a municipality, the higher YLL it has. Further research is needed to better investigate the mechanisms driving such inequalities, particularly regarding the wider role of social determinants of health, which has strong impact on the excess mortality risks.